Characterization Of Unmilled Local Foxtail Millet (Setaria Italica L.) Varieties As Potential Local Food Sources To Support Indonesia'S Food Security - Khairiah Khairiah; Sakina Yeti Kiptiyah; Putri Jasmine Nurfadillah; Amelia Deswita Putri Soleh; Zahra Khairunisa; Islah Nurazizah (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Foxtail millet (Setaria italica L.) is a local cereal with great potential as an alternative food source in Indonesia. Purpose : This study aims to characterize the physicochemical properties of whole-grain foxtail millet flour from three different varieties based on seed color: cream (TXX), red (TYY), and black (TZZ). Methodology: The evaluated parameters included chemical properties (moisture, ash, fat, protein, and carbohydrate contents) and physical properties (thousand-grain weight and color parameters). This study utilized a Completely Randomized Design (CRD). Data were analyzed using ANOVA followed by Tukey’s test at a 5% significance level. Results: The results showed significant differences in moisture content, ash content, thousand-grain weight, and color parameters (p < 0,05). Conversely, fat, protein, and carbohydrate contents were not significantly different among the varieties (p < 0,05). Findings: The black variety exhibited the lowest moisture content (10.23%) and the highest ash content (4.79%), indicating excellent storage stability and high mineral content. The cream variety showed the highest thousand-grain weight (1.26 g) along with a lightness value () of 68.16 and a value of 25.85, reflecting a bright, yellowish flour profile. Novelty: This study demonstrates that the red variety displays the highest value (6.83), which strongly indicates the presence of anthocyanin content. Conclusion: Each variety possesses specific advantages tailored for different product applications; thus, this characterization is essential for optimizing the utilization of foxtail millet in diversifying local Indonesian food sources. Type of Paper: Research paper.